A functional SNP of the core promoter region within goat CDC25A gene affects litter size - Zhang, Taiyuan; Wang, Jingxuan; Bai, Yangyang; Wang, Qian; Wang, Ke; Zhu, Haijing; Qu, Lei; Guo, Zhengang; Pan, Chuanying; Lan, Xianyong (Frontiers in Veterinary Science, 2025)
The Cell division cycle 25A (CDC25A) gene has been considered as a candidate gene associated with reproductive traits for goat breeding. In this study, five truncated fragments divided at position-2285 nt to +198 nt were amplified and cloned into the luciferase reporter vectors to identify the core promoter. The luciferase reporter assay showed that the core promoter of CDC25A was located at position-663 nt to-237 nt. Afterwards, a single nucleotide polymorphism (NC_030829.1:g.51731829A > C) at the core promoter was detected using sequencing and KASP in a population of 1,016 goats and luciferase reporter vectors carrying the A allele or C allele were transfected into cells, respectively. The results displayed that the higher relative luciferase activity was observed in plasmids carrying the A allele rather than the C allele. The litter size of individuals with the AA genotype was significantly better than those with other genotypes, which corresponded to increased transcriptional activity in plasmids carrying the A allele. In short, our study provides a potential molecular genetic marker for improving reproductive efficiency in goat breeding.